2018
DOI: 10.1177/0300060517754032
|View full text |Cite
|
Sign up to set email alerts
|

High doses of minocycline may induce delayed activation of microglia in aged rats and thus cannot prevent postoperative cognitive dysfunction

Abstract: ObjectivePostoperative cognitive dysfunction (POCD) is common after surgery in elderly patients and is associated with high morbidity. The molecular mechanisms responsible for POCD are unknown. Minocycline, an inhibitor of microglial activation, may be useful in treating and preventing POCD. We explored whether minocycline can inhibit microglial activation and prevent POCD in aged rats as a surgery model.MethodsRats aged 18 to 20 months were randomly allocated to the following groups: naïve, abdominal surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In a murine model, it was demonstrated that depleting microglial cells prevented both hippocampal inflammation and cognitive decline after tibial fracture 21 . Pivotal role of microglia was also shown in a rat model of POCD using minocycline to inhibit microglial activation 41 . Surprisingly in this model, the microglial activation was delayed and worsened the cognitive decline after laparotomy in aged rats.…”
Section: Discussionmentioning
confidence: 95%
“…In a murine model, it was demonstrated that depleting microglial cells prevented both hippocampal inflammation and cognitive decline after tibial fracture 21 . Pivotal role of microglia was also shown in a rat model of POCD using minocycline to inhibit microglial activation 41 . Surprisingly in this model, the microglial activation was delayed and worsened the cognitive decline after laparotomy in aged rats.…”
Section: Discussionmentioning
confidence: 95%
“…Li et al. 14 found that rats which received laparotomy presented prolonger escape latency during morris water maze test. Meanwhile, their space exploration and number of crossing platform decreased significantly after laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 14 . found that rats which received laparotomy presented prolonger escape latency during morris water maze test.…”
Section: Discussionmentioning
confidence: 99%
“…A low dose of minocycline (25 mg/kg) showed protective effects, with reduced retinal ganglion cell loss and microglial activation, while a high dose of minocycline (100 mg/kg) showed damage effects, with more retinal ganglion cell loss and microglial activation in mice with retinal ischemia-reperfusion injury (Huang et al, 2018). An in vivo experiment from Li et al also showed that intraperitoneal minocycline treatment (45 mg/kg) may induce delayed activation of microglia in aged rats and thus cannot prevent postoperative cognitive dysfunction (Li et al, 2018). For this reason, although our results do not directly investigate the influence and relevant mechanism of high doses of minocycline (10 and 15 μg/μl) on the neuronal excitability or synaptic strength, the present study suggests the possibility that a high dose of minocycline might regulate cell function in neuronal or non-neuronal cells within the hippocampus of CCI rats.…”
Section: Discussionmentioning
confidence: 99%